An overview of previous research on learning and teaching about mixtures and solutions - Popović, Emina (Norma, 2025)
Summary: The paper analyses previous research in learning and teaching educational content on mixtures and solutions with the goal of improving the teaching process itself and students’ motivation and achievements likewise. In particular, the paper analyses the development of concepts regarding mixtures and solutions, the effects of conceptual change following teaching interventions and the possibilities of initial teaching and learning the contents from the aspect of the particulate nature of matter. Numerous authors refer to the prevalence and rootedness of a number of alternative students’ ideas, but also to teaching strategies that would enable them to be substituted by scientific concepts. The other group of research includes those in which various approaches to teaching mixtures and solutions are analysed. Most findings are indicative of the significance in developing efficient strategies with the goal of improving not only students’ cognitive capabilities and different skills, but also their motivation and attitudes towards teaching science education.Keywords: mixtures and solutions, concepts development, alternative ideas, teaching approaches, natural sciences
Keywords: mixtures and solutions; concepts development; alternative ideas; teaching approaches; natural sciences